Translation and Linguodidactic Problems of The Category of Definiteness and Indefiniteness - Akhmatokhunova Maftunaxon Akmaljon qizi; Valiyeva Navro’zaxon (Periodica Journal, 2022)
This article shows significant features and effective ways of translation of the expressive means of the category of definiteness and indefiniteness in the materials of English and Uzbek languages. In modern Uzbek, indefiniteness is expressed by nouns, for example: The word in a broad generalized sense in terms of the indistinguishability of the constituents of this class of units: "bola - chaqa", "begona".
Keywords: Definiteness; Indefiniteness; Uzbek; English